Tingkat Kenyamanan Pengguna pada Studio Arsitektur: Studi Kasus Studio Arsitektur Institut Teknologi Sumatera - Tri Hartono; Kustiani Kustiani (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2023)
The Architecture Studio is a supporting facility in the Architecture study program where many activities are carried out to carry out assignments. However, there is a tendency that students spend a lot of time outside the studio room doing assignments. Based on these problems, an analysis of user comfort is the aim of this research, especially for students. The research method used in this study is a qualitative method that involves interviewing space users and quantitatively involves taking direct measurements using a tool called a lutron and a windmate in the architecture studio room at the Sumatra Institute of Technology, after which the measurement results are analyzed and compared with the standards set. This research was conducted by paying attention to the differences in lighting in each studio room, the temperature differences in sunny, cloudy, and overcast weather conditions, and the ventilation used in the studio room. From the measurement results, it was found that the lighting conditions in the architectural studio at the Sumatra Institute of Technology did not meet the SNI (Indonesian National Standard, 2001), and the ventilation conditions at the architecture studio at the Sumatra Institute of Technology did not meet the standard for natural ventilation while meeting the standard for artificial ventilation. The architecture studio at the Sumatra Institute of Technology is comfortable carrying out assignments based on an analysis of the activities that take place during studio hours, assistance activities, and the level of work on studio assignments.